Comparison of Diathermy and Scalpel Incision in Inguinal Hernia Repair in Terms of Surgical Site Infection - Butt, Hafiz Khalid Pervaiz; Umair, Bilal; Ali, Adnan; Iqbal, Muhammad Rashid; Ahmed, Aijaz (Infectious Diseases Journal of Pakistan, 2023)
Background: Scalpels are traditionally used for making skin incisions that produce little damage to surrounding tissues. However, potential risk of blood transmitted diseases such as Hepatitis B, Hepatitis C and Human Immunodeficiency Virus (HIV) transmission to both doctor and patient in the presence of scalpel in surgical field promotes continuous surge for identifying other modalities of skin incision. This study aimed to compare the frequency of surgical site infection during inguinal hernia repair between diathermy and scalpel incision in adults who underwent surgical correction at Combined Military Hospital Quetta, Pakistan. Material and Methods: We conducted randomized clinical trial at surgery department in Combined Military Hospital (CMH) Quetta during 15 Sep 2010 to 14 Sep 2011. 212 subjects scheduled for inguinal hernia repair were randomly assigned to either scalpel incision (n=106) or diathermy incision (n=106) by using table of random numbers. Both groups were assessed at post-operative days 2 and 7 for normal healing, mild bruising, erythema with signs of inflammation, clear or hemoserous discharge, pus discharge and tissue separation. Data was recorded on questionnaire. Both groups were compared for superficial surgical site infection and p value for significant difference was calculated by using two sided Chi-Square test. Results: Difference in the frequencies of infection between the two groups (as shown in table 1) was not statistically significant. In Group A, which received scalpel incision, 95 patients had normal healing, 4 patients had mild bruising/ erythema and erythema with signs of inflammation each and 3 patients had clear or hemoserous discharge. In group B, which received diathermy incision 98 patients healed normally, 6 had mild bruising/ erythema, 2 patients had erythema with sings of inflammation and no patient developed hemoserous discharge. Difference between two groups as regards to the development of SSIs is statistically non-significant with p value of 0.47 (as it is more than 0.05). Conclusion: Scalpel incision has no superior advantage over diathermy incision in terms of superficial surgical site infection in elective inguinal hernia repair. Key words: Diathermy, Incision, surgical site infection, scalpel.